Postdisaster Posttraumatic Growth: Positive Transformations Following the Black Saturday Bushfires. Issue 4 (2nd October 2018) - Harms, Louise; Abotomey, Rhonda; Rose, David; Woodward Kron, Robyn; Bolt, Barbara; Waycott, Jenny; Alexander, Melinda
ABSTRACT: Posttraumatic growth (PTG) is emerging in the published literature as an important aspect of postdisaster recovery. Despite these research insights into the positive transformations that people experience, PTG has not been formally operationalised in postdisaster psychosocial recovery efforts. This paper presents findings from a mixed methods study of people affected by the 2009 Victorian "Black Saturday" bushfires. Data from in-depth interviews and the PTG Inventory-Short Form (PTGI-SF) with 20 participants gathered five years after the fires were used to gain new insights into perceptions of postdisaster growth. Higher levels of growth were reported by those who were personally involved. Thematic findings were consistent with most of the PTGI-SF factors. Additionally, growth through connections, the acquisition of new skills, and creative engagement were identified as core growth processes. These processes support conceptualising postdisaster PTG in broader relational terms, rather than more typically psychological ones, which may then inform effective interventions. IMPLICATIONS Many people report posttraumatic growth as part of their disaster recovery experiences. Growth experiences are diverse, and include the acquisition of new skills and connections as well as intrapsychic changes. Social workers can support growth by understanding the complex interaction with trauma experiences. Growth experiences may vary depending upon people's personal and professional disaster involvements.